HOW DOES CAMPUS TEAM SUPPORT MOTIVATION STUDENT CREATIVITY AND INNOVATION (INTERNATIONAL SEMINAR, 2025)
This paper critically examines the role of policing in shaping the control of juvenile delinquency in Indonesia. It aims to understand how young offenders are constructed as “problem youth” within the broader framework of social control and criminal justice. Using a qualitative approach through literature analysis and policy review, the study explores how law enforcement institutions interpret, manage, and discipline juvenile behavior. The findings suggest that police practices often reflect a dual role—balancing the responsibility of protection with mechanisms of surveillance and punishment. This paradox illustrates how juvenile control in Indonesia remains influenced by moral, cultural, and institutional discourses that define acceptable youth behavior. The paper highlights that such policing practices tend to reinforce social hierarchies and gendered norms rather than addressing the structural causes of delinquency. By applying a critical lens, this study contributes to the discourse on juvenile justice reform, emphasizing the need for a more restorative and rights-based approach to youth crime control in Indonesia.